Limits to Neurosurgical Care for an Undocumented Immigrant in the United States: A Case Report - Keener, Myles; Sturges, Rebecca; Becker, Kathryn; Gifford, Connor; Alexander, Christopher; Schroeder, Jason; Smithason, Saksith (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Documentation status is a well-recognized social determinant of health in the immigrant population of the United Sates. Lack of financial means and fear of legal repercussions can delay medical attention, limit treatment options, and decrease patient follow-up. This is reinforced by current government policies that limit financial assistance in emergency situations and deny coverage of preventative or follow-up care. Here we report a case of an otherwise healthy 24-year-old undocumented immigrant who presented to a rural United States emergency room with new-onset seizure, blurry vision, and headache. The patient was admitted to the neurosurgical service where he was diagnosed and treated for a symptomatic arachnoid cyst. Here we review current healthcare legislation that restricts access to preventative and follow-up healthcare in the United States. This case highlights the ways in which the undocumented immigrant patient population remains negatively impacted by these policies, often leading to late presentation and limited neurosurgical treatment options.